CONSUMER PROTECTION FOR LOSSES ARISING FROM THE USE OF AUTO PILOT-BASED TECHNOLOGY IN INDONESIA - Jayvenson Christopher Dellano Here Bessie; Dewa Gde Rudy (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2024)
This study aims to examine the legal safeguards provided to consumers in Indonesia in relation to losses incurred from the use of autopilot-based technology. The research methodology employed in this study is normative legal research, utilizing a legislative approach and legal material analysis. The findings of this study reveal that autopilot technology or artificial intelligence (AI) can be considered as legal entities, as there is human involvement in regulating and operating the technology. However, consumer protection in the utilization of such technology encounters challenges within the Indonesian legal system. This is primarily due to the requirement of reversing the burden of proof for losses under Law Number 8 of 1999 on Consumer Protection. Consequently, this presents a significant hurdle in achieving consumer protection against the adverse effects of this technology, as there exists an imbalance of knowledge and bargaining power between the producer (AI) and the consumer in substantiating the losses incurred from its use.